Geometric analysis of non-degenerate shifted-knots Bézier surfaces in Minkowski space. - Sadia Bashir; Daud Ahmad (PLoS ONE, 2024)
In this paper, we investigate the properties of timelike and spacelike shifted-knots Bézier surfaces in Minkowski space-[Formula: see text]. These surfaces are commonly used in mathematical models for surface formation in computer science for computer-aided geometric design and computer graphics, as well as in other fields of mathematics. Our objective is to analyze the characteristics of timelike and spacelike shifted-knots Bézier surfaces in Minkowski space-[Formula: see text]. To achieve this, we compute the fundamental coefficients of shifted-knots Bézier surfaces, including the Gauss-curvature, mean-curvature, and shape-operator of the surface. Furthermore, we present numerical examples of timelike and spacelike bi-quadratic (m = n = 2) and bi-cubic (m = n = 3) shifted-knots Bézier surfaces in Minkowski space-[Formula: see text] to demonstrate the applicability of the technique in Minkowski space.